Characterization of a Novel Chromosomal Class C β-Lactamase, YOC-1, and Comparative Genomics Analysis of a Multidrug Resistance Plasmid in Yokenella regensburgei W13 - Zhou, Danying; Sun, Zhewei; Lu, Junwan; Liu, Hongmao; Lu, Wei; Lin, Hailong; Zhang, Xueya; Li, Qiaoling; Zhou, Wangxiao; Zhu, Xinyi; Xu, Haili; Lin, Xi; et al. (Frontiers in Microbiology, 2020)
Yokenella regensburgei, a member of the family Enterobacteriaceae, is usually isolated from environmental samples and generally resistant to early generations of cephalosporins. To characterize the resistance mechanism of Y. regensburgei strain W13 isolated from the sewage of an animal farm, whole genome sequencing, comparative genomics analysis and molecular cloning were performed. The results showed that a novel chromosomally encoded class C β-lactamase gene with the ability to confer resistance to β-lactam antibiotics, designated blaYOC-1, was identified in the genome of Y. regensburgei W13. Kinetic analysis revealed that the β-lactamase YOC-1 has a broad spectrum of substrates, including penicillins, cefazolin, cefoxitin and cefotaxime. The two functionally characterized β-lactamases with the highest amino acid identities to YOC-1 were CDA-1 (71.69%) and CMY-2 (70.65%). The genetic context of the blaYOC-1-ampR-encoding region was unique compared with the sequences in the NCBI nucleotide database. The plasmid pRYW13-125 of Y. regensburgei W13 harbored eleven resistance genes (blaOXA-10, blaLAP-2, dfrA14, tetA, tetR, cmlA5, floR, sul2, ant(3’’)-IIa, arr-2 and qnrS1) within an 34 kb multidrug resistance region; these genes were all related to mobile genetic elements. The multidrug resistance region of pYRW13-125 shared the highest identities with those of two plasmids from clinical Klebsiella pneumoniae isolates, indicating the possibility of horizontal transfer of these resistance genes between bacteria of various origins.